Analysis of hygiene indicator bacteria contamination in ready-to-eat foods in Jilin province from 2011 to 2021 - Wei ZHAO; Ruifei ZHANG; Ben SHI; Jingyu SUN; Juan WANG; Xin HUANG; Jingying ZHENG (Zhongguo gonggong weisheng)
ObjectiveTo detect and analyze the contamination of hygiene indicator bacteria in bulk ready-to-eat foods in various regions of Jilin province, providing a reference for the safety supervision of the bulk ready-to-eat food industry in Jilin province. MethodsFrom 2011 to 2021, 5 664 ready-to-eat food samples were collected from 9 regions in Jilin province, including Baicheng city, Baishan city, Jilin city, Liaoyuan city, Siping city, Songyuan city, Tonghua city, Yanbian Korean Autonomous Prefecture, and Changchun city. Four types of hygiene indicator bacteria, including total bacterial count, coliform bacteria, Escherichia coli, and mold, were detected and analyzed. ResultsThe overall pass rate of total bacterial count was 82.19% (3563/4335), the overall pass rate of coliform bacteria was 63.34% (1617/2553), the overall pass rate of Escherichia coli was 96.5% (1655/1715), and the overall pass rate of mold was 72.07% (240/333). Among the 9 monitored cities, Tonghua city had the lowest pass rate of total bacterial count at 58.53% (367/627), with a mean value of (4.41 ± 1.51) lgCFU/g; Baishan city had the lowest pass rate of coliform bacteria at 43.48% (100/230), with a mean value of (3.47 ± 1.34) lgCFU/g; Tonghua city had the lowest pass rate of Escherichia coli at 92.54% (310/335), with a mean value of (2.11 ± 0.87) lgCFU/g; and Songyuan city had the lowest pass rate of mold at 54.17% (13/24), with a mean value of (2.13 ± 1.04) lgCFU/g. Among different types of foods, salads had the lowest pass rate of total bacterial count at 0, with a mean value of (5.70 ± 0.71) lgCFU/g; Chinese-style cold dishes had the lowest pass rate of coliform bacteria at 15.13% (23/152), with a mean value of (3.49 ± 1.08) lgCFU/g; salads had the lowest pass rate of Escherichia coli at 94.34% (150/159), with a mean value of (1.88 ± 0.61) lgCFU/g; and cakes had the lowest pass rate of mold at 32.26% (10/31), with a mean value of (3.08 ± 1.98) lgCFU/g. Among different sampling locations, small restaurants had the lowest pass rate of total bacterial count at 74.74% (494/661), with a mean value of (4.14 ± 1.35) lgCFU/g; The qualified rates of Escherichia coli and Escherichia coli in department stores are the lowest, at 28.95% (11/38) and 80.00% (4/5), respectively. The average value of Escherichia coli is (4.06 ± 1.21) lgCFU/g, and the number of positive samples for Escherichia coli is 2.04 lgCFU/g; and convenience stores had the lowest pass rate of mold at 53.33% (24/45), with a mean value of (2.41 ± 1.00) lgCFU/g. ConclusionThe contamination levels of hygiene indicator bacteria in bulk ready-to-eat foods that do not undergo a final heating step, such as raw foods, cold dishes, and filled foods, are relatively high in different regions of Jilin province and should be prioritized for prevention. Small and medium-sized restaurants, fast food restaurants, and department stores have higher contamination rates of hygiene indicator bacteria and require focused supervision and management.